Catalytic effect in Li-S batteries: From band theory to practical application. (July 2022) - Han, Zhiyuan; Gao, Runhua; Jia, Yeyang; Zhang, Mengtian; Lao, Zhoujie; Chen, Biao; Zhang, Qi; Li, Chuang; Lv, Wei; Zhou, Guangmin
Graphical abstract: In this review, the key issues that how to observe, understand, design, and use catalytic effect in Li-S batteries are systematically discussed. A research paradigm for catalytic effect is further proposed, which will enlighten the future development of Li-S batteries and other next-generation batteries based on conversion reactions. Abstract: Lithium-sulfur (Li-S) batteries with high energy density have been considered one kind of promising next-generation energy storage system. However, the shuttling effect of polysulfides caused by the intrinsic sluggish reaction kinetics severely hinders their commercialization. The catalytic effect, a powerful solution towards polysulfides shuttling by accelerating the conversion of polysulfides, has aroused great attention. Numerous catalysts have been developed and proved to have catalytic effects in the past years. More importantly, many advanced in-situ characterization technologies and electronic structure analyses have been combined to study the "black box" of the catalytic process, which promotes the practical application of Li-S batteries entering a new stage. In this review, instead of summarizing recent achievements in catalyst materials and structural designs, the key issues that how to observe, understand, design, and use catalytic effect in Li-S batteries are systematically discussed. In-situ techniques are summarized to see the actual catalytic process. Band theory is applied to understand the electronic structure, thus deciphering design principles and strategies of catalytic effect. Subsequently, how to use the catalytic effect to realize Ah-level Li-S pouch cells is analyzed. Last, we propose a research paradigm for catalytic effect, which will enlighten the future development of Li-S batteries and other next-generation batteries based on conversion reactions.